Quantitative Trait Loci for Freezing Tolerance in a Lowland x Upland Switchgrass Population - Poudel, Hari P.; Sanciangco, Millicent D.; Kaeppler, Shawn M.; Buell, C. Robin; Casler, Michael D. (Frontiers in Plant Science, 2019)
Low-temperature related abiotic stress is an important factor affecting winter survival in lowland switchgrass when grown in northern latitudes in the USA. A better understanding of the genetic architecture of freezing tolerance in switchgrass will aid the development of lowland switchgrass cultivars with improved winter survival. The objectives of this study were to conduct a freezing tolerance assessment, generate a genetic map using single nucleotide polymorphism (SNP) markers, and identify QTL (quantitative trait loci) associated with freezing tolerance in a lowland x upland switchgrass population. An pseudo-F2 mapping population was generated from an initial cross between the lowland genotype Ellsworth and the upland cultivar Summer. The segregating progenies were screened for freezing tolerance in a controlled-environment facility. Two clonal replicates of each genotype were tested at six different treatment temperatures ranging from -15 to -5°C at an interval of 2°C over two time periods. Tiller emergence (days) and tiller number were recorded following the recovery of each genotype. Survivorship of the pseudo-F2 population ranged from 89% at -5°C to 5% at -15°C with an average LT50 of -9.7°C. Genotype had a significant effect on all traits except tiller number at -15°C. A linkage map was constructed from bi-allelic single nucleotide polymorphism markers generated using exome capture sequencing. The final map consisted of 1618 markers and 2626 cM with an average inter-marker distance of 1.8 cM. Six significant QTL were identified, one each on chromosomes 1K, 5K, 5N, 6K, 6N and 9K for the following traits: tiller number, tiller emergence days and LT50. A comparative genomics study revealed important freezing tolerant genes/proteins such as COR47, DREB2B, zinc finger-CCCH, WRKY, GIGANTEA, HSP70, and NRT2 among others that reside within the 1.5 LOD confidence interval of the identified QTL.